2006
DOI: 10.1029/2006jd007080
|View full text |Cite
|
Sign up to set email alerts
|

Space‐based near‐infrared CO2 measurements: Testing the Orbiting Carbon Observatory retrieval algorithm and validation concept using SCIAMACHY observations over Park Falls, Wisconsin

Abstract: [1] Space-based measurements of reflected sunlight in the near-infrared (NIR) region promise to yield accurate and precise observations of the global distribution of atmospheric CO 2 . The Orbiting Carbon Observatory (OCO) is a future NASA mission, which will use this technique to measure the column-averaged dry air mole fraction of CO 2 (X CO 2 ) with the precision and accuracy needed to quantify CO 2 sources and sinks on regional scales ($1000 Â 1000 km 2 ) and to characterize their variability on seasonal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
185
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(193 citation statements)
references
References 63 publications
2
185
0
Order By: Relevance
“…The ACOS-GOSAT data processing algorithm is based on the optimal estimation approach of Rodgers (2000) and is described in detail in O'Dell et al (2012). It is modified from the OCO retrieval algorithm (Bosch et al, 2006;Connor et al, 2008;Boesch et al, 2011) to account for the different physical viewing geometries and properties such as instrument line shapes and noise models.…”
Section: H Nguyen Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…The ACOS-GOSAT data processing algorithm is based on the optimal estimation approach of Rodgers (2000) and is described in detail in O'Dell et al (2012). It is modified from the OCO retrieval algorithm (Bosch et al, 2006;Connor et al, 2008;Boesch et al, 2011) to account for the different physical viewing geometries and properties such as instrument line shapes and noise models.…”
Section: H Nguyen Et Almentioning
confidence: 99%
“…We make a simplifying assumption that the annual and seasonal trends are constant over the hemispheres. We aggregate daily CarbonTracker X CO 2 values over both the Northern and Southern Hemisphere for the entire 2-year period, and we compute the trend coefficients {c 0 (s), c 1 (s), a(s), θ (s)} using variable transformation and linear regression (Artis et al, 2007). The resulting coefficients are displayed in Table 1.…”
Section: Trend Termsmentioning
confidence: 99%
“…They have shown that SCIAMACHY can accurately capture the seasonal cycle in X CO 2 due to vegetation growth on monthly time scales. Bösch et al [33] use X CO 2 Park Falls data to reveal biases in the SCIAMACHY data. De Beek et al [34], Buchwitz et al [35] and Reuter et al [36,37] have significantly improved the SCIAMACHY retrieval algorithms, again using TCCON data as their ground reference.…”
Section: (B) Satellite Validationmentioning
confidence: 99%
“…The greenhouse gas retrievals described in Bösch et al (2006) and O'Dell et al (2012) use this approach to derive column amounts of greenhouse gases alongside aerosol properties. In this particular case, x comprises elements related to aerosols (such as aerosol profiles for various types or microphysical properties as in Butz et al, 2009) Table 1.…”
Section: Retrieval Setupmentioning
confidence: 99%
“…As opposed to ground-based direct sun spectra such as from the TCCON network (Wunch et al, 2011), the exact light-path distribution of recorded photons is not known from the nadir space-borne viewpoint, causing ambiguities between light-path and trace-gas amount changes. To mitigate this general retrieval problem, full-physics algorithms (e.g., Bösch et al, 2006;Boesche et al, 2009;Butz et al, 2009;O'Dell et al, 2012) simultaneously fit multiple channels using radiative transfer calculations, concurrently retrieving X CO 2 , X CH 4 , surface albedos as well as a set of aerosol properties, the prime contributor to photon pathlength changes. Also for SCIAMACHY (Bovensmann et al, 1999), multi-band retrievals have been developed fitting the O 2 A-band and a weak CO 2 band at moderate spectral resolution (Reuter et al, 2010).…”
Section: Introductionmentioning
confidence: 99%